Combined Styrene/MMA/Nanoclay Cross-linker Effect on Wood-Polymer Composites (WPCs) - Md. Rezaur, Rahman; Josephine, Chang Hui Lai; Sinin, Hamdan; Abu Saleh, Ahmed; Rubiyah, Baini; Shanti Faridah, Saleh (BioResources, 2013)
In the present study, batai wood (Paraserianthes moluccana) was impregnated with a combination of styrene, methyl methacrylate, and nanoclay in order to improve compression strength, thermal stability, and surface morphology. Styrene (ST) and methyl methacrylate (MMA) cross-linker introduced a co-polymerization reaction with cellulose in the wood cell wall and produced wood polymer composites (WPCs), as confirmed by Fourier Transform Infrared (FT-IR) Spectroscopy. The mechanical properties of the WPCs were significantly increased compared to the raw wood. Thermal properties of both raw wood and WPCs were evaluated by thermogravimetric analysis (TGA). WPCs exhibited higher thermal stability relative to the raw wood due to the co-polymerization reaction. The surface morphologies of the fracture surface for both the raw wood and WPCs were recorded using scanning electron microscopy (SEM). The SEM micrographs reveal that after polymerization, WPCs show smoother texture and adhesion compared to that of raw wood.